Almond Rootstocks: Overview - Rubio-Cabetas J.M. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
Almond growing has significantly changed over the last decades in the. Production has decreased in some countries such as but in others, including, an important change has taken place. The possibilities for choosing a rootstock have also significantly increased. The use of almond seedlings has always been linked to rainfed conditions and peach seedlings to irrigated conditions. The peach x almond hybrid ‘GF- has been the rootstock most utilized in the past years, either for rainfed or irrigated conditions. Nowadays, however, with the high demand for these crops and the new areas planted in substitution of other fruit crops, new rootstock releases are being used more often, mainly newly-bred Spanish rootstocks. The rootstock choice must respond to better management, adaptability to different soil types, and resistance to nematodes. The studies of compatibility with plum species, especially the selection and use of some clonal almond x peach hybrid rootstocks have increased the selection possibilities considerably. In this situation, the red-leaved and rootknot nematode-resistant almond x peach hybrids (GxN) that are well adapted to Mediterranean conditions due to their ‘Garfi’ parentage, in both irrigated and non-irrigated conditions (mainly ‘Garnem’), have become the predominant rootstocks. Particularly noteworthy among the recent releases has been the incorporation of root-knot nematode (RKN) resistance. Special emphasis has also been placed on developing dwarfing rootstocks for high-density orchard systems. New hybrid rootstocks of complex origin are now under experimentation and initial results indicate that they could improve almond production if they fulfil the requirements of modern fruit growing, as discussed in this revision.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)